Sustainable Competitive Advantage through Information Technology Competence: Resource-Based View on Small and Medium Enterprises - J. W., Ong; Bin Ismail, Hishamuddin (2008)
Information and communication technology (ICT) has been the main focused of Malaysian government to strengthen the small and medium enterprises (SMEs) in the country. However, scholars in resource-based view acknowledge that sustainable competitive advantage can only be achieved through building a co-specialised ICT competence between the human factors and ICT facilities in the firm. In the context of SMEs, the entrepreneur is expected to become the agent for the integration. In order to do so, the entrepreneur must be equated with sufficient ICT knowledge. This knowledge can be acquired through either education or experience. The framework developed is then tested through 365 sets of primary data collected from the entrepreneurs in SMEs in Malaysia. SPSS version 15 is used to analyse the data. The results of statistical analysis have supported the framework proposed. Managerial implications and conclusion are then discussed.